Formation of nano and micro scale hierarchical structures in MgO and ZnO quantum dots doped LC media: the role of competitive forces - A. K. Singh; S. P. Singh (Condensed Matter Physics, 2023)
In this paper, we have studied the effect of doping of ZnO and MgO nanoparticles (NPs) in 4-(trans-4-n-hexylcyclo-hexyl) isothiocyanatobenzoate. A thorough comparison of dielectric properties, optoelectronic properties, and calorimetric phase transition properties has been done for MgO and ZnO NP doped LC. We prepare their homogenous mixture of MgO and ZnO NPs in toluene and transfer into cells made of glass and Indium Tin-Oxide (ITO) coated glass. The observed microstructures in the hybrid system can be classified into three main categories: grain like structures formed by aggregation of smaller size MgO nanoparticles while liquid crystal molecules anchor over the surfaces of nanoparticles, the grtu grain-like structures further integrate to form inorganic polymeric type of honeycomb-like mesostructures in presence of glass surface, and flower-like clusters of MgO nanoparticles on ITO surface. The smaller size nanoparticles can maintain the energy balance by allowing the anchoring of liquid crystal molecules over their surfaces whereas the larger size nanoparticles cannot compromise or maintain the energy balance with the liquid crystal molecules and are separated out to nucleate and form bigger size nanoaggregate or clusters. The energy preference of the substrate and nanoparticle’s surface to liquid crystal molecules plays an important role in the formation of different types of hierarchical nano- and microstructures. We account the reasons for the formation of nano and micro scale hierarchical structures on the basis of the competition between the forces: NP-NP, LC-LC, NP-LC, Glass/ITO-NP, and Glass/ITO-LC interactions. We observed a considerable change in the dielectric properties, transition temperature, bandgap, and other parameters of LC molecules when MgO NPs are doped, but a minor change occurs when ZnO NPs are doped in LC. Optical microscopy, FTIR, Raman, IR, HR-XRD and FESEM-EDX characterization data confirm and validate our guiding conceptions.